Et du coté des enseignants ? Processus d’historicisation et développement professionnel. Réponse à Anne-Sophie Cayet - Nathalie Thamin (Recherches en didactique des langues et des cultures)
This article is part of Axis 3 of the NEQ 2023 Day: "Approaching the interpreting subject by placing teachers and researchers in history". The dialogue with A-S. Cayet proposes an articulation between the approach to the subject-teacher, the reflexive posture and the professional identity solicited/suscitated within the framework of training courses designed and collaborative research aimed at teachers and their professional development in a diverse context (Huver and Bel, 2015): how/in what way do training courses constitute spaces that involve historicization, reflexivity, agentivity? What approaches and activities are likely to foster them? What are the points of tension?